Heat and charge carrier flow through single-walled carbon nanotube films in vertical electrolyte-gated transistors: implications for thermoelectric energy conversion - Ueji, Kan; Muto, Nobuhiro; Heimfarth, Daniel; Matsuoka, Yuya; Ichinose, Yota; Yomogida, Yohei; Yagi, Takashi; Zaumseil, Jana; Yanagi, Kazuhiro (ACS applied nano materials, 2022)
Understanding the relationship between electrical and thermal characteristics of thin ﬁlms is crucial for their thermal management. However, there are hardly any reliable experimental data on this relationship because measurement methods that can evaluate both characteristics in the same direction are very limited. Here, we report a measurement technique that can simultaneously evaluate electrical and thermal characteristics by combining time-domain thermoreﬂectance and vertical electrolyte-gated transistors. We demonstrate that the thermal conductivity of single-walled carbon nanotube ﬁlms is independent of the vertical current density, which is modulated over 4 orders of magnitude, indicating a route to improve thermoelectric conversion eﬃciencies.
Gesehen am 28.08.2022